2011
DOI: 10.1039/c1dt10929d
|View full text |Cite
|
Sign up to set email alerts
|

Local structure of Mn4+ and Fe3+ spin probes in layered LiAlO2 oxide by modelling of zero-field splitting parameters

Abstract: The zero-field splitting parameters (ZFS) of Mn(4+) and Fe(3+) ions in LiAlO(2) with a layered structure are analyzed experimentally and theoretically by using high-frequency electron paramagnetic resonance spectroscopy, Neuman superposition model (NSM), DFT and multiconfigurational calculations. The interpretation of ZFS is based on the comparison of the experimentally determined values with the calculated ones. This approach allows assessing the performance of different methods for computation of ZFS of Fe(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…This experimental tool allows us to distinguish the hexagonal and orthorhombic P2-structures of Na 2/3 MnO 2 with respect to the Mn 4+ and Mn 3+ ions. 11,32,33 For the hexagonal P2-Na 2/3 MnO 2 containing only Mn 4+ ions, the EPR spectrum consists of a single Lorentzian line with a g-value of 1.996 and a line width of 75 mT. For the orthorhombic P2-Na 2/3 MnO 2 containing both Mn 3+ and Mn 4+ ions, the EPR signal is broadened significantly reaching a value of 300 mT and the g-factor deviates strongly from 1.99 approaching a value of 1.72.…”
Section: Resultsmentioning
confidence: 99%
“…This experimental tool allows us to distinguish the hexagonal and orthorhombic P2-structures of Na 2/3 MnO 2 with respect to the Mn 4+ and Mn 3+ ions. 11,32,33 For the hexagonal P2-Na 2/3 MnO 2 containing only Mn 4+ ions, the EPR spectrum consists of a single Lorentzian line with a g-value of 1.996 and a line width of 75 mT. For the orthorhombic P2-Na 2/3 MnO 2 containing both Mn 3+ and Mn 4+ ions, the EPR signal is broadened significantly reaching a value of 300 mT and the g-factor deviates strongly from 1.99 approaching a value of 1.72.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the Os III congener is more promising than Ru III due to the stronger SOC but also because of its better stability [254]. (133), which was synthesized by the treatment of [Mn(acacen)(CH 3 OH) 2 ]PF 6 with (Ph 4 P) 3 [Os(CN) 6 ]. [255].…”
Section: Ru-and Os-based Metallo-ligandsmentioning
confidence: 99%
“…when the quantum energy provided by the EPR spectrometer ( h ν , 0.3 cm –1 /9.4 GHz and 1.2 cm –1 /34 GHz at X- and Q-band frequencies, respectively) is much larger than the magnitude of D . Therefore, for systems with | D | > ∼0.2 cm –1 , high-frequency and -field EPR (HFEPR) is required (from 3 cm –1 /95 GHz up to 33 cm –1 /1 THz). In the special case of Mn IV ( d 3 ; S = 3/2), numerous X-band EPR studies have been reported, but only rarely D -values were determined as they are frequently too large for the X-band energy quantum. More recently, a combined X- and Q-band EPR investigation, as well as a few HFEPR ones, have shown that the expected range of D values in Mn IV is moderate, from 0.2 cm –1 up to 1.65 cm –1 . However, unlike for Mn III and Mn II , no systematic investigation of Mn IV in complexes involving different types of coordination sphere (nature of the ligands, coordination number) has been reported so far, avoiding definition of magnetostructural correlation.…”
Section: Introductionmentioning
confidence: 99%